Much ado about "nuthin" : the origins of the cosmos and a unified theory of everything : science fiction? or science fact? - Corlis, Brian, 1935-; Corlis, Helen R ([Glenmore Park, N.S.W.] : [Brian E Corlis], 2021)
"The proposed Nuthin/Sumthin Model describes the origins and subsequent nature of the Cosmos in three dimensional states of energy. The Primary dimension described as "Nuthin", with the property of gravity, and the Secondary dimension described as "Sumthin", with its property of anti-gravity,exist in opposite states of polarity, and are the "missing" dark matter and dark energy respectively. The fundamental "Nuthin dimension" is the entity which provides all the mass, either directly or indirectly, in the Cosmos. The "Sumthin dimension" is derived from the "Nuthin dimension" at an infinite number of singularity events spread across the Cosmos described as "Galactic Expansion Events". The two primary dimensions are only evident by the creation of the "Ethin dimension" being a neutral dipole of "nuthin and sumthin" at their interface. This third state of energy represents all visible matter. This model also introduces concepts such the Cosmic Cycle, Gravitational focal points, Reverse Singularity, as well as a new concept for symmetry, spin and atomic structure." -- page 5.
"Editor: Helen R. Corlis" -- verso title page.
"First published Jan 2020, Current version: 2021/08/04" -- verso title page.
Title from title screen.
Includes bibliographical references.
For secondary school age.
Mode of Access: Available online.
Keywords: Dark matter (Astronomy); Hydrogen; Matter; Dark matter (Astronomy); Hydrogen; Matter; Electronic books; Academic Dissertation; Academic theses